Comparison of the acute effects of different exercise modalities applied with myofascial relaxation technique on ankle flexibility and swimming performance in swimmers - AGOPYAN, ANİ (My University, 2022)
Foam rolling is a self-myofascial release technique that is commonly used to improve range of motion. However, insufficient research investigates the acute effects of using the foam roller on soft tissue extensibility and muscular performance in young age group athletes. Studies examining the acute effects of land warm-up models consisting of different SMR exercises on performance in the water, especially in swimmers, are limited. Therefore, this study aims to compare the acute effects of different models of SMR (non-vibrating and vibrating foam roller) used in the warm-up phase on the range of motion of ankle joint and lower extremity swimming performance components of 11-12-year-old swimmers Nineteen healthy girl swimmers (age/year: 11.07±11.42) at the competitor level were included in the study. All participants’ ankle joint range of motion in dorsal and plantar flexion (degree-Kinovea 0.9.5 application) and 25m-50m (using kickboard, swimming goggles, and snorkel) lower extremity swimming performance components (swimming time, foot strike speed, and foot kicking number) of all participants were recorded and measured with a video camera on 3 different test days. In addition, 3 different warm-up models were applied to the athletes. a) only land and water warm-up; after the land and water warm-up on different days randomly, 3 different warming models were applied with b) vibration foam roller (speed-1800R) and c) non-vibration foam roller (Livepro-LP8236). Foam roller exercises were applied to m.Quadriceps, m.Gluteus Maximus, m.Hamstrings, m.Triceps Surea-(Calf) and Plantar Fascia respectively. The scope of the exercise was planned as 2 minutes in total for each zone (4 sets, 30 seconds each), 20-25 seconds between movements, and 10 seconds between sets. In the data evaluation, the Shapiro-Wilk test was used for normality analysis, a one-way analysis of the variance-Friedman test for differences between repeated measurements, and Spearman correlation analysis was used to determine the relationships between parameters. The exercise models which used in the study did not make any difference in lower extremity swimming performance components and ankle range of motion (p>0.05). In addition to land and water warm-up, it was determined that different models of SMR were not superior to the other in increasing ankle flexibility and lower extremity swimming performance components. Although the exercises applied do not provide an increase in performance, they can be used as an alternative warm-up model before short-distance kicking exercises in swimming training.

Köpük silindir, kendi başına uygulanan miyofasyal gevşeme (SMR) yöntemlerinden biri olup, sıklıkla eklem hareket açıklığını arttırmak için kullanılmaktadır. Ancak köpük silindirin küçük yaş grubu sporcularında kullanılmasının, yumuşak dokunun uzayabilirliliğine ve kassal performanstaki akut etkilerine yönelik araştırmalar yetersizdir. Özellikle yüzücülerde farklı SMR egzersizlerden oluşan kara ısınma modellerinin sudaki performansa olan akut etkilerini inceleyen araştırmalar sınırlıdır. Bu yaklaşımla araştırmamızda, ısınma evresinde kullanılan SMR’nin farklı modellerinin (titreşimli ve titreşimsiz köpük silindir) 11-12 yaş grubu yüzücülerde ayak bileği eklem hareket açıklığına ve alt ekstremite yüzme performans bileşenlerindeki akut etkilerinin karşılaştırılması amaçlanmaktadır. Araştırma kapsamına yarışmacı düzeyinde 19 sağlıklı kız yüzücü (yaş/yıl:11,07±11,42) alındı. Tüm katılımcıların 3 farklı test gününde ayak bileği dorsal ve plantar fleksiyon eklem hareket açıklığı (dereceKinovea 0.9.5 uygulaması), 25m-50m (ayak tahtası, yüzme gözlüğü ve şnorkel kullanılarak) alt ekstremite yüzme performans bileşenleri (yüzme süresi, ayak vuruş hızı ve sayısı) video kamera ile kaydedilerek ölçüldü. Ayrıca sporculara; a)sadece kara ve su ısınması; randomize olarak farklı günlerde kara ve su ısınmasının ardından b) titreşimli (hız-1800R) ve c) titreşimsiz köpük silindir (LiveproLP8236) ile 3 farklı ısınma modeli uygulatıldı. Köpük silindir egzersizleri sırasıyla m.Quadriceps, m.Gluteus Maximus, m.Hamstrings, m.Triceps Surea-(Calf) ve Plantar Fasya’ya uygulandı. Egzersizin kapsamı; her bölge (4 set, 30’ar sn) için toplamda 2dk, hareketler arasında 20-25sn ve setler arasında 10sn dinlenme süresi olacak şekilde planlandı. Verilerin değerlendirilmesinde; normallik analizi için Shapiro-Wilk testi, tekrarlı ölçümler arasındaki farklılıklar için tek yönlü varyans analizi-Friedman testi, parametreler arasındaki ilişkilerin belirlenmesinde Spearman korelasyon analizi kullanıldı. Kullandığımız egzersiz modelleri, alt ekstremite yüzme performans bileşenlerinde ve ayak bileği eklem hareket açıklıklarında bir farklılık oluşturmadı (p>0,05). Kara ve su ısınmasının yanı sıra, SMR’ın farklı modellerinin de ayak bileği esnekliğini ve alt ekstremite yüzme performans bileşenlerini arttırmada, birinin diğerinden üstün olmadığı belirlendi. Uyguladığımız egzersizler performansta bir artış sağlamamasına rağmen, yüzme antrenmanlarında kısa mesafe ayak vuruş çalışmaları öncesinde, alternatif bir ısınma modeli olarak kullanılabilir.
Yüzücülerde miyofasyal gevşeme tekniği ile uygulanan farklı egzersiz modellerinin ayak bileği esnekliğine ve yüzme performansına olan akut etkilerinin karşılaştırılması
Keywords: Foam roller; flexibility; swimming; Köpük silindir; esneklik; yüzme